PERAN MULTIMEDIA BERBASIS WEBSITE TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Ainol Ainol; Loviga Denny Pratama; Wahyu Lestari; Novi Ayu Yulia (Mandalika Mathematics and Educations Journal, 2023)
This study aims to determine the effect of using web-based multimedia on learning mathematics on student learning outcomes. This research uses quantitative research in the form of quasi-experimental with non-equivalent post-test only control group design. The research population was Ar-Rofi'iyyah Islamic High School students with the research object being students of class XI IPS 1 as the experimental class and XI IPS 2 as the control class. Hypothesis testing using one sample t-test and independent sample t-test. Based on data analysis, it appears that there is a significant effect of the use of web-based multimedia in mathematics lessons on student learning outcomes. This can be seen from the calculation of the t-test for mathematics learning outcomes that obtain a Sig. (2-tailed) (0.000)≤α(0.05). Based on the decision criteria, H0 is rejected and Ha is accepted so that it is proven that the use of website-based multimedia in mathematics learning has an effect on student learning outcomes